Kimura’s disease with atypical musculoskeletal presentation - Zulkifly, Ahmad Hafiz; Aziz, Yusuf; Ismail , Rosmaliza; N., Premchandran; Ramachandran, Kalavathy (Malaysian Orthopaedic Association, 2010)
We would like to highlight an unusual clinical presentation of Kimura’s disease, a rare, benign, idiopathic condition, usually seen as swelling and lesions of the head and neck region and commonly affecting young men of Asian descent. It is rare for this disorder to present with lesions on other parts of the body, especially the lower limbs. We report a 27- year-old man who presented with a large mass located at the inguinal region and extending down to the upper thigh. Due to the large size of the mass (28 x 18 cm), our provisional diagnosis was a soft tissue sarcoma. Open biopsy showed that the lesion was benign.